Pengaruh Dimensi Keadilan, Pengetahuan Pajak, Sanksi Pajak, Moral Wajib Pajak Dan Komunikasi Setelah Pemberlakuan Pp No. 46 Terhadap Tingkat Kepatuhan Wajib Pajak UMKM(Studi Empiris Pada Wajib Pajak Pelaku UMKM yang Terdaftar di KPP Pratama Karanganyar) - wahyu, Haris Triono, Dr. Zulfikar, SE, M.Si (2016)
The background of this research on the issuance of PP 46 Year 2013 which enforment is still quite difficult because of the taxpayers who have the perception that this policy is less fair. In particular, this study aims to analyze the influence of the dimensions of justice, knowledge of taxes, tax penalties, a taxpayer morale and communication after the implementation of PP 46 on tax compliance STO SMEs in Karanganyar. Research conducted with quantitative approach survey method through questionnaires. Analysis of data using multiple linear regression analysis The population is all SMEs that business gross income of less than 4,8M per year in Karanganyar district. The sampling technique was conducted using simple random sampling was taking members of the sample of the population was randomly without regard to strata that exist in the population with solvin formula approach. The results showed simultaneous variable dimensions of justice, knowledge of tax, penalty taxes, moral taxpayer and communication effect on tax compliance SMEs in STO Karanganyar and partially variable dimensions of justice, knowledge of tax morale of taxpayers and communication affect the compliance Mandatory Taxes SMEs in STO Karanganya whereas tax sanctions have no effect on tax compliance STO SMEs in Karanganyar